Coronavirus Infection in Children (Situation on February 2020) - Leyla S. Namazova-Baranova; Alexandr A. Baranov (Union of pediatricians of Russia, 2020)
Considering the raft of information about the coronavirus infection in the Internet most of which cannot be considered not only as evidence-based medicine but even as proven or scientific, we are going to perform analysis of published literature and present you all the up-to-date data on coronavirus infection in the world in our journal in every issue.